تناوب الإجهاد الستاتيكي على قدرة تحمل واستقرار ألواح العناصر السندويشية بطبقتي تغطية معدنيتين تأثير ونواة من مادة البوليؤريتان /PUR/ - صقور, أكرم (Latakia University Journal -Engineering Sciences Series, 2016)
تُنتج محلياً ألواح سندويشية مؤلفة من طبقتي تغطية معدنيتين تفصلهما التصاقاً نواة سميكة من مادة رغوية متصلبة من البوليؤريتان. يتوسع انتشار هذه الألواح يوماً بعد يوم كعناصر إنشائية تحاكي المستلزمات الوظيفية للمنشأة الهندسية. استخدام هذه الألواح كعناصر إنشائية حاملة في منشآت جدارية أو سقفية يمكن أن ينجم عنه تبدل في طبيعة الإجهاد الناظمي المؤثر على مواد مقاطعها، وخصوصاً طبقتي التغطية فيها نتيجة لإمكانية تناوب انعطاف جزء اللوح استاتيكياً، أو ديناميكياً، سواء أكان التناوب ناتجاً عن تبدل اتجاه تأثير التحميل عليه، أم تناوب التحميل الإضافي على الفتحات المتجاورة للجمل المستمرة منه. يجري تقييم قدرة تحمل واستقرار هذه الألواح السندويشية استناداً إلى قيمة الإجهاد الحرج المؤدي إلى تشكل أمواج التجعيد لطبقة التغطية المضغوطة للوح، والذي ترتبط قيمته بالدرجة الأولى بجودة وخصائص المنتج ميكانيكياً وفيزيائياً. تناول البحث اختبار قدرة تحمل اللوح السندويشي المنتج محلياً واستقراره نتيجة التناوب استاتيكياً في طبيعة إجهاده كعنصر إنشائي حامل في الجملة الإنشائية المشكلة من مثل هذه الألواح. لقد أظهرت نتائج البحث أن هذا اللوح المنتج محلياً يسلك سلوكاً خطياً، أيضاً،حتى في حال تبدل اتجاه انعطافه أو طبيعة إجهاد طبقة التغطية فيه، خصوصاً في مراحل التحميل المرافقة لتشكل إجهاد التجعيد الحرج على الأقل، بينما تنخفض قيمة هذا الإجهاد الحرج بمقدار 40% عن قيمته لحالة تحميل اللوح أو تعرضه لعزم انعطاف باتجاه واحد فقط. Sandwich panels are locallyproduced with two faces of metal those which covera hard adhesive and thick core of polyurethane. The widely Extend of these panels increase day for day as structural elements imitating the function necessities of the engineering construction. The use of those panels as carried structural elementsin wall or ceiling structures can coincide with a submission of their sections materials, especially the two faces to the change in a nature of the normal stress acted on them due to the alternate of the panel part bending statically or dynamically when the alternatewas produced from the changeof the loading acting directon it or from the alternate of the live loading on the adjacent fields of the continuous systemsfrom it. The evaluation of the sustaincapacity and stability of the sandwich elements consisted of such panels performsdepended to the critical stress value leaded to arise of the wrinkling waves of the compressive face of the panel that it values depended first on the quality and properties of the production. The research handledthe testing of the sustainabilityand stability of the local produced sandwich paneldue to the alternate in a nature of it stress statically as a carried structural element in the structural system built from such panels. The conclusionsof the research showedthat this produced panel followsalinearbehavior too even in the case of the change of its bendingdirection orstress natureof itsface, especially in the loading steps coincidedat least to thearising of the critical wrinkling stress, whereasthe value of this stress decreases 40% from its value for the loading or bending case of the panel in only one direction.